Warm Electromagnetic Forming of AZ31B Magnesium Alloy Sheet - Arroyo, A.; Eguiy, I.; Gutiérrez, M. A.; Hurtado, I.; Ulacia, I. (Institut für Umformtechnik - Technische Universität Dortmund, 2010)
Historically, electromagnetic forming technology has mainly been used to form parts from aluminium and copper alloys due to their excellent electrical conductivity and limited formability by conventional methods. However, little research has been carried out in high strain rate forming of magnesium alloy sheets. Therefore, in the current contribution electromagnetic forming experiments are performed for rolled AZ31B magnesium alloy sheet at different temperatures up to 250°C. Two forming operations are studied in this paper, i.e. drawing and bending operations. The final deformations achieved for the different conditions were measured and the effect of both temperature and discharged energy on deformation is shown. Bending experiments at room temperature were recorded by means of a high speed camera and the springback behaviour at high strain rates is evaluated. In one hand, increasing the forming temperature the yield strength of the material decreases while on the other hand, the electrical conductivity and thus the induced forces are also decreased. It is observed that increasing the forming temperature, for a given discharged energy, the maximum height of the deformed part is decreased. However, increasing the discharged energy at warm temperatures, higher deformation values are achieved without failure. Additionally, bending experiments show that springback effect is also decreased at warm conditions. It is concluded that warm electromagnetic forming is a suitable procedure to manufacture magnesium parts.
Keywords: electromagnetic forming; magnesium alloy; warm forming; 620; 670